The American Islamic Community: Which Muslims are Likely to be Encouraged by Other People?. Issue 44 (15th March 2018) - Hodge, David R.; Zidan, Tarek; Husain, Altaf
ABSTRACT: Encouragement—or expressions of support designed to instill perseverance and hope in the face of challenging circumstances—is an important concept in the strengths perspective and a central feature of social work practice. Encouragement may be a particularly significant factor for Muslims living in post-9/11 America. Yet, little research has examined this topic despite its relevance. To address this gap in the literature, this cross-sectional study employed a community sample of Muslims ( N = 274) to identify which Muslims are disproportionately likely to report receiving expressions of support from other people. The results of the logistic regression indicated that Muslims who were single, Middle Eastern, non-Sunni, and frequent Mosque attenders, were more likely to receive expressions of support compared to those who were married, European American, Sunni, and less frequent Mosque attenders. Conversely, Muslims without a 4-year college education and born aboard were less likely to receive expressions of support compared to those with a graduate degree and born in the US. The paper concludes by offering a tentative explanation for the results and suggesting some implications for practice with Muslim clients. Future researchers might build upon the findings by replicating the study with nationally representative samples.